2019
DOI: 10.4187/respcare.06992
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Step Count and Clinical Frailty in Hospitalized Adults With Community-Acquired Pneumonia

Abstract: BACKGROUND: In adults hospitalized with community-acquired pneumonia (CAP), increasing ward-based walking may reduce length of stay (LOS). There are few data to describe ward-based walking in this population. In adults hospitalized with CAP, we aimed to report variables of walking and non-walking time, to determine whether demographic or clinical variables influenced daily step count, and to determine whether daily step count influenced LOS. METHODS: Following admission, daily step count and variables related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 41 publications
4
18
2
Order By: Relevance
“…Rice et al reported a median walking time of 66 min/day (IQR 41-121 min/day) in hospitalized patients with CAP. 23 This is almost fourfold longer than in the present study (14 min/day; IQR 4-26 min/day), and might be explained by differences in age, severity of pneumonia and epochs of accelerometer data between the two samples. Participants in the study by Rice et al were younger (66.8 AE 18.2 years) and had less severe pneumonia (confusion, urea, respiratory rate, blood pressure and age ≥65 years [CURB-65 1; IQR 1-2) than the present sample (82 years; IQR 75-89 years, ADROP 2; IQR 1-2).…”
Section: Discussioncontrasting
confidence: 58%
“…Rice et al reported a median walking time of 66 min/day (IQR 41-121 min/day) in hospitalized patients with CAP. 23 This is almost fourfold longer than in the present study (14 min/day; IQR 4-26 min/day), and might be explained by differences in age, severity of pneumonia and epochs of accelerometer data between the two samples. Participants in the study by Rice et al were younger (66.8 AE 18.2 years) and had less severe pneumonia (confusion, urea, respiratory rate, blood pressure and age ≥65 years [CURB-65 1; IQR 1-2) than the present sample (82 years; IQR 75-89 years, ADROP 2; IQR 1-2).…”
Section: Discussioncontrasting
confidence: 58%
“…Part of the problem is that higher-level injuries result in loss of innervation to motor neurons that innervate the diaphragm and intercostal muscles, resulting in compromised respiratory motor control (reviewed in [ 18 ]). The lack of mobility in SCI persons also exacerbates this issue since exercise, like walking and running, has been shown to reduce pneumonia-related mortality [ 19 , 20 , 21 , 22 ]. However, what may make respiratory infections particularly deadly for SCI persons is that higher injuries above the level of thoracic segment 6 (T6) result in disruption of descending supraspinal input to sympathetic preganglionic neurons (SPNs) that innervate immune organs and modulate immune function, which we describe in more detail in a later section.…”
Section: The Consequences Of Peripheral Immune Dysfunctionmentioning
confidence: 99%
“…Hospitalization is associated with bed rest which can result in prolonged physical inactivity and immobilization. In fact, patients hospitalized with CAP spent over 90% of their waking hours being physically inactive, i.e., either laying or sitting down, with only 926 steps per day during admission [ 6 , 7 ]. Moderate to severe frailty is a predictor of lower daily step count.…”
Section: Introductionmentioning
confidence: 99%
“…Moderate to severe frailty is a predictor of lower daily step count. It has been reported that frail patients take 59% less steps per day during admission compared to robust patients [ 6 ], which can exacerbate physical deterioration several weeks after discharge [ 8 ]. Frail patients with frequent readmissions may be prone to a more rapid decline in functional ability and associated deteriorations in health-related quality of life [ 9 ], which may cause a viscous cycle of physical inactivity with negative effect on the prognosis [ 10 12 ] (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation